2005
DOI: 10.1016/j.devcel.2005.04.014
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Dynamics of Clathrin and Its Adaptor-Dependent Recruitment to the Actin-Based Endocytic Machinery in Yeast

Abstract: Clathrin-mediated transport is a major pathway for endocytosis. However, in yeast, where cortical actin patches are essential for endocytosis, plasma membrane-associated clathrin has never been observed. Using live cell imaging, we demonstrate cortical clathrin in association with the actin-based endocytic machinery in yeast. Fluorescently tagged clathrin is found in highly mobile internal trans-Golgi/endosomal structures and in smaller cortical patches. Total internal reflection fluorescence microscopy showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
218
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 169 publications
(230 citation statements)
references
References 59 publications
10
218
2
Order By: Relevance
“…However, Newpher et al (24) reported that in sla2Δ cells Ent1-GFP exhibited Merged images of Sla1-GFP and Abp1-RFP in epsin-depleted (tetENT1, ent2Δ) and sla2Δ strains are shown. The images of the epsin-depleted strain were taken before (− doxycycline) and after (+ doxycycline) the depletion of Ent1.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…However, Newpher et al (24) reported that in sla2Δ cells Ent1-GFP exhibited Merged images of Sla1-GFP and Abp1-RFP in epsin-depleted (tetENT1, ent2Δ) and sla2Δ strains are shown. The images of the epsin-depleted strain were taken before (− doxycycline) and after (+ doxycycline) the depletion of Ent1.…”
Section: Resultsmentioning
confidence: 97%
“…To perform FRAP experiments in wild-type cells, we arrested endocytosis with latA, which allows the assembly of the endocytic coat but blocks vesicle budding (11,19,24). Ent1-GFP recovery in latA-treated wild-type cells was very slow, indicating that Ent1 binds to the endocytic site in a stable manner (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To generate cells expressing GFP-Clc1, a 3.5-kb EcoRI/NotI fragment from pTMN17 (Newpher et al, 2005) containing the coding sequence for GFP-Clc1 was ligated with EcoRI/NotI digested pRS306 to generate pJRC7. pJRC7 was digested with PacI to linearize the plasmid in the CLC1 region for targeted integration.…”
Section: Integration Of Gfp-clc1mentioning
confidence: 99%
“…GFP-LC is a suitable marker for localizing HC within yeast cells as GFP-Clc1 has been shown to completely colocalize with the fluorescent signal of Chc1-RFP (Newpher et al, 2005). GFP-LC localizes to the TGN, endosomes, and small cortical patches.…”
Section: Visualization Of Clathrin and Endocytic Dynamics In Td Mutantsmentioning
confidence: 99%
See 1 more Smart Citation